Flagellin-specific human CAR Tregs for immune regulation in IBD - Boardman, Dominic A.; Wong, May Q.; Rees, William D.; Wu, Dan; Himmel, Megan E.; Orban, Paul C.; Vent-Schmidt, Jens; Zachos, Nicholas C.; Steiner, Theodore S.; Levings, Megan K. (Journal of autoimmunity, 2023)
Regulatory T cell (Treg) therapy is a promising strategy to treat inflammatory bowel disease (IBD). Data from animal models has shown that Tregs specific for intestinal antigens are more potent than polyclonal Tregs at inhibiting colitis. Flagellins, the major structural proteins of bacterial flagella, are immunogenic antigens frequently targeted in IBD subjects, leading to the hypothesis that flagellin-specific Tregs could be an effective cell therapy for IBD. We developed a novel chimeric antigen receptor (CAR) specific for flagellin derived from Escherichia coli H18 (FliC). We used this CAR to confer FliC-specificity to human Tregs and investigated their therapeutic potential. FliC-CAR Tregs were activated by recombinant FliC protein but not a control flagellin protein, demonstrating CAR specificity and functionality. In a humanized mouse model, expression of the FliC-CAR drove preferential migration to the colon and expression of the activation marker PD1. In the presence of recombinant FliC protein in vitro, FliC-CAR Tregs were significantly more suppressive than control Tregs and promoted the establishment of colon-derived epithelial cell monolayers. These results demonstrate the potential of FliC-CAR Tregs to treat IBD and more broadly show the therapeutic potential of CARs targeting microbial-derived antigens. •Chimeric antigen receptors (CAR) can be used to confer microbe specificity to Tregs.•Flagellin-specific CAR Tregs preferentially home to damaged intestinal tissues.•CAR Tregs elicit antigen-dependent immunosuppression.•Activated CAR Tregs secrete factors that promote intestinal barrier integrity.